2021
DOI: 10.1177/87569728211037775
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Analysis of Unethical Behaviors in Projects: Insight From Moral Psychology

Abstract: Ethical aspects of stakeholder behavior can have a wide range of implications for other areas of project management. This research critically reviewed project ethics under the philosophical paradigm change from modernism to late modernism, which led to a flexible and realizable ethical framework based on Levinasian and Nietzschean moral psychologies. A qualitative approach was adopted through a multiple-case study to confront the theoretical framework with the empirical world, evaluate its authenticity, and ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Leicester (2016) found that project managers generally found codes of ethics not to be necessary and less useful as ethical guidance than organizational processes and guidelines, good judgment, and an internal moral code. This view is mirrored by Sarhadi and Hasanzadeh (2022), whose examination of four cases revealed both a desire to adhere to ethical codes (when project managers were aware of them) and organizational rules, but also an awareness that these do not cover all moral obligations. Context around ethical decisions and conflicting stakeholder outcomes on projects always make an impact, yet how much of an effect and at what point in the project manager’s ethical analysis or decision-making process these contextual factors are considered is not clear.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Leicester (2016) found that project managers generally found codes of ethics not to be necessary and less useful as ethical guidance than organizational processes and guidelines, good judgment, and an internal moral code. This view is mirrored by Sarhadi and Hasanzadeh (2022), whose examination of four cases revealed both a desire to adhere to ethical codes (when project managers were aware of them) and organizational rules, but also an awareness that these do not cover all moral obligations. Context around ethical decisions and conflicting stakeholder outcomes on projects always make an impact, yet how much of an effect and at what point in the project manager’s ethical analysis or decision-making process these contextual factors are considered is not clear.…”
Section: Introductionmentioning
confidence: 95%
“…This work argues for the superiority of a third approach that follows from Aristotelian ethics, which emphasizes instilling and exhibiting positive values. These three central ethical positions are mirrored in the work of Sarhadi and Hasanzadeh (2022) and Ljungblom and Lennerfors (2018). Xu and Smyth (2023), in contrast, reference and seek to provide an alternative to "dominant moral or ethical theories," which include Kantian (rules based), Aristotelian (values), and utilitarian (consequentialist) views.…”
Section: Introductionmentioning
confidence: 99%
“…Happily, in recent years, we have observed a small yet growing community of project scholars interested in the dark side, including corruption (Locatelli et al, 2017; Osei-Tutu et al, 2010; Owusu et al, 2019), sexism (Henderson et al, 2013; Pinto et al, 2017), modern slavery (Brookes et al, 2020), and greenwashing (He et al, 2021). Such topics are traditionally considered inconvenient and uncomfortable to research and therefore tend to remain hidden, both as a phenomenon and a field of study.…”
Section: The Rationalementioning
confidence: 99%
“…In "A Qualitative Analysis of Unethical Behaviors in Projects: Insight From Moral Psychology," Sarhadi and Hasanzadeh (2021) discuss ethics in projects. The topic is important, as project actors walk a fine line between what they consider to be morally admissible and what is required for projects and themselves to succeed.…”
Section: Accepted Articlesmentioning
confidence: 99%
“…In project studies, there is a growing number of articles published about ethics (Müller et al, 2013(Müller et al, , 2014Sarhadi & Hasanzadeh, 2022) and social sustainability (Kivilä et al, 2017;Martens & Carvalho, 2017;Sabini et al, 2019;Sabini & Alderman, 2021). However, project studies literature is mostly silent on a relevant phenomenon: modern slavery.…”
Section: Introductionmentioning
confidence: 99%